PENGARUH DEWAN KOMISARIS INDEPENDEN, KEPEMILIKAN INSTITUSIONAL DAN INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PERUSAHAAN - Fatimah Fatimah; Putri Dwi Wahyuni (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2020)
This study aimed to determine the effect of Independent Board of Commissioners, Institutional Ownership and Intellectual Capital on Company’s Financial Performance. The Company's financial performance is proxied by NPM (Net Profit Margin). This study uses multiple linear analysis methods with hypothesis testing the coefficient of determination, f test and t test. The population in this study are transportation services companies listed on Indonesia Stock Exchange 2016-2018 period. Based on the purposive sampling method. there is the final data in this study. The results of this study indicate that the Independent Board of Commissioners and Intellectual Capital don’t have a significant effect on the Company's Financial Performance (NPM), while Institutional Ownership has a significant effect on the Company's Financial Performance (NPM).